Illinois basis regression models - Bailey, Jacob (Kansas State University, 2014)
The commodity markets have seen a great deal of volatility over the past decade, which, for those involved, has created many challenges and opportunities. Some of those challenges and opportunities are related to the behavior of the basis – the difference between the local cash price of grain and its price in the futures market. This thesis examines factors impacting basis for corn and soybeans at an Illinois River barge terminal, inland grain terminals in central Illinois, and in the Decatur processing market. Factors used to explain basis behavior include the price level of futures markets, the price spread in the futures market, transportation cost, local demand conditions, and seasonal patterns. Using weekly data on basis from 2000 to 2013, regression models indicate that nearby corn futures, futures spread, inverted market, days until expiration, heating oil futures, and some months are significant drivers of corn basis. For inland terminals and processor regression models nearby corn futures do not appear to have significant effects. Using the same parameters for soybean basis nearby soybean futures, futures spread, inverted market, heating oil and some months are significant drivers but days until expiration do not appear to have a significant effect.
Keywords: Basis; Regression; Futures; Commodities; Spreads; Illinois; Agriculture, General (0473); Business (0310); Economics, Agricultural (0503)